Association of long-term exposure to PM2.5 in workplace with fasting plasma glucose among asymptomatic adults: A multicenter study in North China. (August 2022) - He, Jiangshan; Hu, Songhua; Xu, Ximing; Guo, Pei; Niu, Yujie; Zhang, Jingbo; Zhang, Rong; Chen, Shuo; Ma, Shitao; Liu, Feng; Li, Qiang; Li, Chunjun; et al.
Graphical abstract: Highlight: Exposure to PM2.5 could elevate asymptomatic adults' fasting plasma glucose. Abstract: Background: The impacts of long-term high exposure to PM2.5 in workplace on glucose metabolism in asymptomatic working adults (AWAs) have rarely been explored. Objectives: To assess the relationship between long-term exposure to workplace PM2.5 and glucose metabolism in asymptomatic general working adults in heavily polluted regions. Methods: We used the baseline data of the asymptomatic working participants from the Beijing-Tianjin-Hebei Medical Examination Cohort, which recruited adults undergoing medical examinations. A machine learning-based spatial–temporal model was used to estimate daily average PM2.5 concentrations in the participants' workplaces. We assessed the association of long-term PM2.5 concentrations (three years prior to the interview) and fasting plasma glucose (FPG) using generalized linear mixed-effects models (GLMM) with inclusion of potential confounders. Stratified analyses by sex, age, BMI and smoking status, and two pollutant models were further performed. Results: A total of 37, 619 individuals were interviewed and 28, 865 were included in the analyses. The mean FPG was 5.20 (0.96) mmol/L, and the estimated three-year average concentration of PM2.5 exposure was 69.51 (6.92) μg/m 3 . We detected a significant association of long-term exposure to workplace PM2.5 and FPG, a 10 µg/m 3 increase in the long-term workplace PM2.5 exposure was associated with 0.075 (95%CI: 0.050–0.100) mmol/L elevated FPG and 25% (OR = 1.25, 95%CI: 1.05–1.50) elevated odds of abnormal fasting glucose metabolism with control of the potential confounding. The detected association between workplace PM2.5 and FPG metabolism remained significant in males, individuals aged > 44 years, overweight and/or obese people, both smokers and non-smokers, and when NO2, SO2, O3, and CO were included in the model. Conclusions: Long-term exposure to workplace PM2.5 was associated with elevated FPG and/or odds of abnormal glucose metabolism among AWAs. Male, middle-aged, overweight and/or obese AWAs were more susceptible to workplace PM2.5 regardless of smoking status.